Identifikasi Komposisi Kimia Tar Kayu Mahoni untuk Biofuel pada Berbagai Temperatur Pirolisis - Wijayanti, Widya (Jurnal Rekayasa Mesin, 2018)
This study indentified the tar yield of pyrolysis of mahogany wood. The produced tar would be analyzed using GC-MS (Gas Chromatograph-Mass Spectrometry) to understand their chemical properties affected by temperature pyrolysis. It would be identified if the elements are flammable matters or not. It is due to the fact that the yields of pyrolysis desire the flammable matters as much as possible as a biofuel. The experiment was conducted at a fixed bed reactor. The needle particle of mahogany wood was used as the pyrolysis feedstock having weight of 200 gram, sizing of mesh 20 hm, and containing 2% moisture content. The variations of pyrolysis temperature influencing the mahogany wood decompositions are 250°C, 350°C, 450°C, 500°C , 600°C, 700°C and 800°C. The pyrolysis was carried out during 3 hours almost without Oxygen. The result of tar yields show that a getting higher of the pyrolysis temperature caused the volume and mass of tar formed by condensation in cold trap would increase up to 500°C and then decrease. The increasing of tar yields would also increase some acetic acid compounds and reach a peak at 350°C in which the acetic acid compound is a flammable substance. From the GC-MS results, it was also presented that at any pyrolysis temperatures, the amount of the flammable tar compounds were higher than the unflammable one. It can be interpreted that the tar yield is very potential as liquid fuel (bio-oil) because the main elements of tar is acetic acid having flash point (flash point) equal to 39°C.